Role of Embolization in the Treatment of Renal Masses - Li, David; Pua, Bradley B.; Madoff, David C. (Seminars in Interventional Radiology, 2014)
Renal arterial embolization (RAE) performed for the treatment of renal masses has been proven to be a safe and effective technique, with several decades of experience. RAE is well tolerated with few complications, particularly if the time interval from embolization to surgery is reduced to less than 48 hours. Review of the literature suggests that RAE is also extremely effective for palliation of symptoms in the setting of nonoperative advanced stage renal cell carcinoma. In addition, this technique plays a large role in the management of angiomyolipomas that are symptomatic or at risk of spontaneous rupture. To date, RAE has not been evaluated in a randomized controlled setting, which has contributed to its underutilization. All of these potential benefits warrant the need for prospective studies for further validation.
Keywords: embolization; renal cell carcinoma; angiomyolipoma; preoperative; interventional radiology